Evaluation of Bethesda system for reporting thyroid cytology with histopathological correlation - Reddy, Purushotham; Prakash, Akina; S. Giriyan, Sujata (International Journal of Research in Medical Sciences, 2017)
Background: The Bethesda system of reporting thyroid cytopathology is a standardised system, improving communication between cytopathologists and clinicians, leading to more consistent management approaches. The aim of the research work was to study the utility of Bethesda system in reporting thyroid cytology with histopathological correlation of all the cases undergoing surgical resection. Methods: We studied all the thyroid cytology cases received between November 2012 to April 2014, and classified them according to the Bethesda system. Histopathological correlation was done for all the cases which underwent surgical resection with evaluation of cyto-histological discrepancies. Results: Out of 484 cases studied, 432(89.2%) were benign lesions, 20(4.1%) were malignant,18 (3.7%) were Unsatisfactory/Nondiagnostic, 10(2%) were Follicular neoplasm/Suspicious for neoplasm, 3 (0.6%) were suspicious for malignancy, and 1(0.002%) case was reported as Atypia of undetermined significance. Out of the 54 cases available for histopathological follow-up, cyto-histological discrepancies were noted in 5 cases (9.2%). Statistical analysis of the present study showed that cytological analysis of thyroid lesions by Bethesda system has got high sensitivity (72.72%), high specificity (95.3%) with a positive predictive value of 80% and negative predictive value of 93.1% and a high accuracy (90.7%). Conclusions: Reviewing the thyroid FNAs (fine needle aspirates) using Bethesda system allowed a more specific cytological diagnosis with better interlaboratory agreement. As evidenced by its high sensitivity and specificity, Bethesda system has proven to be a very effective guide for the clinical management of thyroid nodules.